Factor and simplify. Express the answer as a fraction without negative exponents:
2x(2x-1)^(-1/2) - 2(2x-1)^(1/2)
so your question now is
$\displaystyle
\frac{2x}{\sqrt{2x-1}}-2\sqrt{2x-1}
$
$\displaystyle
=\frac{2x-2\sqrt{2x-1}\sqrt{2x-1}}{\sqrt{2x-1}}
$
$\displaystyle
=\frac{2x-4x+2}{\sqrt{2x-1}}
$
$\displaystyle
=\frac{2-2x}{\sqrt{2x-1}}
$
Multiplying numerator and denominator by$\displaystyle (2x-1)^\frac{1}{2}$to convert the negative powers into positive
$\displaystyle
=\frac{(2-2x)\sqrt{2x-1}}{{\sqrt{2x-1}}^2}
$
$\displaystyle
Ans=\frac{2(1-x)(2x-1)^{\frac{1}{2}}}{2x-1}
$